Exploring healthcare staff experiences with a hybrid paper/digital health management information system and their perspectives on digitalization as an alternative – A Tanzanian qualitative case study on perinatal data - Mary Cronin; Lucy Munishi; Gaudensia A. Olomi; Modesta Mitao; Blandina T. Mmbaga; Jackline Somi; Jairy Khanga; Ali S. Khashan; Francis M. Pima; Simon Woodworth (PLoS ONE, 2025)
Quality health data is essential to improve delivery and outcomes of healthcare. This study explores the experiences of healthcare staff in Kilimanjaro, Tanzania, using a hybrid paper and digital Health Management Information System, and their perspectives on transitioning to a fully digital system. It aims to understand current practices of perinatal data collection and utilisation and gather recommendations regarding the possible introduction of a fully digital HMIS (DHMIS). A case study design was employed; individual semi-structured interviews were undertaken with staff from four professions directly involved in data generation and use ( n = 29 ), working in a range of healthcare settings. Thematic analysis was conducted using NVivo 12 software; it identified findings under four major themes, along with a series of recommendations on the implementation of the DHMIS. We found that while in theory the hybrid paper and digital system facilitates standardised data management, in practice it presents inefficiencies in manual data entry leading to challenges with data accuracy, loss, retrieval, storage and flow. These challenges contribute to the strongly positive attitude among healthcare staff towards adopting a DHMIS which they believe would improve data accuracy, reduce workload, and enhance clinical and policy decision-making. To achieve a successful DHMIS, participants recommended effective training for all users. Additionally, they proposed an integrated system to avoid data redundancy. The importance of robust infrastructure to ensure sustainability, and of reliable internet and electricity supply, were also highlighted. In conclusion, this study provides valuable insights into the shortcomings of paper-based perinatal data recording, and the potential benefits and challenges of implementing a DHMIS in low-resource settings. It underscores the necessity of strategic planning, investment in infrastructure, and capacity building to achieve successful digital transformation in healthcare. The findings align with global health strategies promoting digitalisation to enhance health outcomes and support data-driven decision-making in healthcare systems.